The Lack of the English Lab and Its Effects on Students’ Listening Skills: The Case of the Second-Year Students from English Departments in Kinshasa - Larice Toko Lumanda (RIRAI Publisher, 2022)
This article is based on the fact that there is lack of English language laboratory in the institutions of higher education. The research problem is that the students in these institutions have difficulties to develop their listening skills. Since the students in these institutions are taught by non-native speakers of English, they are exposed to a kind of English influenced by the lecturers’ mother tongues or French. As English is taught in the institutions of higher education in Kinshasa as a Foreign Language, the English Language Lab becomes indispensable to develop the students’ listening skills. Therefore, the research question of this paper is “what are the effects of the lack of the English Language Lab on the students’ listening skills?” So the aim of this paper is to investigate into the second-year students’ listening skills so as to find out the effects of the lack of the English Language Lab on the students under study. The hypothesis is that the effects are inabilities to discriminate the English sounds and to grasp the words uttered with high speed. To reach the aim, a listening test was used to collect data and the content analysis was used to analyze them. The results confirmed the hypothesis and the discussion showed that without an English Language Lab, students cannot develop their listening skills.